The Solar Response Factor to calculate the cooling load induced by solar gains. (15th December 2015) - Evola, G.; Marletta, L.
Highlights: The paper introduces a new methodology to calculate the cooling load in buildings. The approach is based on the calculation of the Solar Response Factor (SRF). The SRF measures the response to solar heat gains in terms of attenuation and delay. The reliability is checked against simulations on EnergyPlus with excellent results. Examples are provided about its usefulness and significance. Abstract: This paper introduces an original approach for the evaluation of the cooling load due to the solar radiation incident on the glazed surface of a building. This approach is based on a newly introduced parameter called Solar Response Factor, defined as the overall convective heat flux released by the building envelope to the indoor space per unit radiant heat flux acting on the outer surface of the glazing. The Solar Response Factor is a complex number, and can be calculated as a combination of the thermal and the optical properties of walls and glazing. In particular, the paper discusses how the Solar Response Factor depends on the optical properties of the envelope, on the size of the windows and on the type of walls delimiting the enclosed space. Furthermore, under steady-periodic conditions, the use of the Solar Response Factor allows an easy analytical estimation of the cooling load due to solar gains. The reliability of this approach is successfully proven by comparison with a series of simulations carried out with EnergyPlus. The results provide very useful information for optimizing the thermal response of an enclosure to periodic solar heat gains.